Determination of Damage Severity on Rotor Shaft Due to Crack Using Damage Index Derived from Experimental Modal Data. Issue 5 (4th April 2012) - Ong, Z.C.; Rahman, A.G.A.; Ismail, Z.
<x xml:space="preserve">Abstract</x> After long duration of an operation, a shaft under high spin speeds and heavy loadings may develop fatigue cracks. This could lead to catastrophic failure and could be difficult to detect. An accurate prediction of dynamic characteristics of rotor system is fundamentally important. Hence, a practical method to nondestructively locate and estimate the severity of a crack in terms of its damage index by measuring the changes in natural frequencies of the rotor shaft is presented. In this study, experimental modal analysis (EMA) data were utilized. A crack detection algorithm to locate and identify cracks in the rotor system using the first and second natural frequencies was outlined. Subsequently, a crack‐locating model was formulated by relating the fractional changes in modal energy to the changes in natural frequencies as a result of cracks based on the experimentally obtained natural frequencies and mode shapes' functions. The feasibility and practicality of the crack detection scheme were evaluated for several damage scenarios by locating and sizing cracks in test rotor shafts for which the first two natural frequencies were available. It was observed that crack could be confidently located with a relatively small localization error. It was also observed that crack severity could be estimated in terms of its damage index.